CHARACTERISTICS OF CHILD VIOLENCE AND ITS NEGATIVE CONSEQUENCES - Gulbakhor Abdullayevna Gaynazarova (Лучшие интеллектуальные исследования, 2023)
Abstract. In the 20th and 21st centuries, all types of violence spread widely around the world. Violence against children is manifested in various forms and methods. The article gives recommendations to adults regarding violence against children, their types, characteristics, and consequences.